Keanekaragaman Genetik Tanaman Pisang (Musa sp.) di Indonesia: Pendekatan Molekuler dan Implikasinya untuk Konservasi dan Pemuliaan - S, Sutriana (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study examined the genetic diversity of local bananas (Musa spp.) from various key regions in Indonesia, including Ambon, Raja, Kepok, Klutuk, Tanduk, Barangan, Batu, and Susu varieties. Through experimental and descriptive approaches using microsatellite analysis (SSR), ITS-PCR-RFLP, rbcL barcoding, and flow cytometry, high genomic variations (AA, AAB, ABB) and ploidy levels (diploid, triploid, tetraploid) were found in local cultivars. Molecular markers and morphological data showed consistent classification and great potential for the development of banana varieties resistant to major diseases such as BSV and Panama disease. The results of this study emphasise the importance of the genetic diversity of local Indonesian bananas as a key resource for breeding programs, germplasm conservation, and the resilience and sustainability of national banana production.